The Relationship between Healthy Eating Patterns, Physical Activity, and Physical Fitness: A Systematic Literature Review on Junior High School Students - Yunus, Moch; Hanief, Yulingga Nanda; Ramadhan, Muhammad Putra; Kurniawan, Agung; Manggolono, Lintang Nirmalasari Gemalochaya; Septiananda, Farsya Hidayah; Ismalasari, Rini (Indonesian Journal of Advanced Research, 2025)
Healthy eating patterns and physical activity are two crucial factors that influence physical fitness, especially among junior high school students. This study utilizes a Systematic Literature Review (SLR) method to explore the relationship between healthy eating, physical activity, and physical fitness. Relevant articles were selected based on inclusion criteria, such as focusing on junior school students, using empirical data, and being published within the last 10 years. The results reveal that a healthy diet rich in nutrients, such as complex carbohydrates, proteins, vitamins, and minerals, significantly contributes to improving students’ physical endurance and bodily functions. Regular physical activity, such as exercise, has been shown to enhance muscle strength, flexibility, and cardiovascular function. Furthermore, the combination of healthy eating and physical activity demonstrates a significant synergistic effect on physical fitness, creating metabolic balance and reducing the risk of obesity and non-communicable diseases. This study emphasizes the importance of a holistic approach in consistently applying healthy eating patterns and physical activity among junior high school students. The implementation of nutrition education and physical activity programs in schools is a key recommendation to improve students' physical fitness.